Automobile component manufacturing method
Patent Information
- Application Number
- JP2024101022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2024-06-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-06-24
AI Technical Summary
【0029】 本発明においては、前記樹脂が弾性率45MPa以上かつ延性10%以上となるようにサンドイッチ構造部材を仮焼きする仮焼き工程を備えたことにより、プレス成形時の樹脂のはみ出しと破断を共に防止できる。 また、サンドイッチ構造を形成した後に部品形状にプレス成形するので、本体部品とパッチを一度にプレス成形できる。したがって、各部品を個々にプレス成形していた従来例と比べて工程数を削減でき、サンドイッチ構造を有する自動車部品を低コストに製造できる。
Smart Images

Figure 2025026323000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an automobile part having a sandwich structure in which resin is sandwiched between steel plates. [Background technology]
[0002] The front side member, which is a structural component of an automobile, is a long part installed at the front of the vehicle in the longitudinal direction of the vehicle, and absorbs the collision energy during a vehicle collision by undergoing axial crushing deformation. In addition, the side sill (rocker) and center pillar are parts that absorb collision energy by bending when a collision load is input from the side of the vehicle body. By absorbing the collision energy during a vehicle collision, these parts suppress cabin deformation during the collision and protect the occupants.
[0003] The above-mentioned front side members, side sills (rockers), and center pillars need to be able to reliably absorb the energy of a vehicle collision, and so require a structure that controls the deformation mode. On the other hand, since automotive parts are also required to be lightweight, technologies have been proposed to combine resins with the above-mentioned parts to improve collision energy absorption performance and rigidity while also reducing weight (multi-material parts).
[0004] Patent Document 1 discloses an automobile collision energy absorption part that absorbs collision energy by axially collapsing when a collision load is input from the front or rear of the vehicle body. The automobile collision energy absorption part of Patent Document 1 can also improve vibration damping by absorbing vibrations from the automobile engine and vibrations input to the vehicle body from each direction while the vehicle is running. Furthermore, Patent Document 2 discloses a vehicle body frame part that bends when a collision load is input from the side of the vehicle body to absorb collision energy.
[0005] In both of the parts in Patent Documents 1 and 2, resin is applied or affixed to the inner surface of a metal main body member (a cylindrical member, a hat-shaped cross-section member, or a U-shaped cross-section member), and a metal anti-detachment member with a U-shaped cross-section is disposed so as to cover the surface of the resin. By disposing resin on the inner surface of the main body member, the resin is sandwiched between the steel plates during axial crushing, in which the part is crushed in an accordion-like manner in the axial direction, or bending crushing, in which the part is bent perpendicular to the axial direction, so that the bending radius during deformation is enlarged, making the main body member less likely to break, and improving collision energy absorption performance. As described above, the parts in Patent Documents 1 and 2 have a sandwich structure in which resin is sandwiched between a metal main body member and a metal anti-detachment member, thereby preventing fracture of the main body member in the event of axial crush or bending crush, improving collision energy absorption performance while also achieving weight reduction. Many methods have been proposed for manufacturing components having such a sandwich structure in which resin is sandwiched between metal plates.
[0006] Patent Document 1 describes a method for manufacturing a part having a sandwich structure by applying or sticking resin to the inner surface of a cylindrical member, arranging a separation prevention member to cover the resin, joining the separation prevention member to the cylindrical member, and then heat-treating these members. Patent Document 1 also describes a method for applying or sticking resin to the separation prevention member, abutting the resin against the inner surface of the cylindrical member and joining the separation prevention member to the inner surface of the cylindrical member, and heat-treating these members.
[0007] Furthermore, Patent Document 3 discloses a frame structure (center pillar) of a vehicle body in which a filler (such as epoxy resin) is foamed and filled into the space between the outer panel and the reinforcement, and describes the following method for assembling the frame structure. First, a sheet of unfoamed filler is attached to the surface of the reinforcement facing the outer panel. The reinforcement with the attached filler is then attached to the outer panel, and the flanges of both are joined by spot welding. After the assembly of the entire vehicle body is completed, the vehicle body is electrocoated, and the drying heat used in this process causes the filler to foam and harden.
[0008] Furthermore, Patent Document 4 describes the following method as a manufacturing method for a partial composite vibration-damping part for automobiles to prevent automobile noise. First, a resin having vibration-damping properties is applied to a restraining plate made of a steel plate or the like, and the solvent in the paint on the restraining plate is evaporated in a drying oven. After that, the restraining plate is attached to a predetermined position of a steel plate that is to be press-formed to form the vehicle body, and heated and pressed. Then, the steel plate to which the restraining plate is partially bonded is press-formed to produce a composite vibration-damping part for an automobile.
[0009] Patent document 5 also discloses a method for manufacturing a metal plate member, in which first and second metal plates are overlapped with a resin adhesive interposed therebetween, the first and second metal plates are press-molded, and the resin adhesive is hardened after press molding.
[0010] Patent Document 6 also discloses a vehicle body manufacturing method in which a first body member and a second body member are joined via a damping adhesive, the damping adhesive in a portion that will become the lower end region in the assembly position of the joined body is temporarily cured, and then the joined body is joined to a third body member so as to assume the assembly position. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2020-100183 A [Patent Document 2] JP 2020-117039 A [Patent Document 3] JP 2001-048054 A [Patent Document 4] Japanese Patent Application Publication No. 11-141005 [Patent Document 5] Patent Publication No. 2020-183078 [Patent Document 6] Patent Publication No. 2021-126930 Summary of the Invention [Problem to be solved by the invention]
[0012] As described above, various methods have been proposed for manufacturing components having a sandwich structure in which resin is sandwiched between metal plates. However, these manufacturing methods have the following problems.
[0013] First, in the manufacturing method of Patent Document 3, since the filler is foamed and filled into the closed cross-sectional space formed in the existing parts such as the outer panel of the center pillar and the reinforcement, the locations where the resin can be placed are limited. Therefore, there is a problem that the parts that show the effect of vibration damping and rigidity cannot be reinforced arbitrarily.
[0014] In contrast, the manufacturing method of Patent Document 1 involves applying or attaching resin to a tubular member and then attaching an anti-detachment member to cover the resin, making it possible to place resin in any location where rigidity needs to be increased (for example, the punch shoulder R portion of the outer part that constitutes the tubular member). However, the above manufacturing method requires an additional press molding step for the anti-detachment member in addition to the press molding step for the cylindrical member, which increases the manufacturing cost.
[0015] In addition, in the manufacturing method of Patent Document 1, since the resin is applied or attached to the member after press molding, it may be difficult to apply or attach the resin with a uniform thickness to the part where the surface of the member has an uneven shape. Therefore, there is a problem that the part to which the resin is applied or attached is limited to a part having a relatively smooth surface with few unevenness.
[0016] In contrast, the manufacturing method of Patent Document 4 applies resin to a steel plate (constraint plate) before press forming, so it is less subject to restrictions due to the uneven surface shape of the area to which the resin is applied after press forming. Furthermore, after the constraint plate is partially adhesively joined to the steel plate (blank), these are integrally press formed, so no additional press forming process is required. However, in the above manufacturing method, the resin-coated restraining plate is attached to a steel plate (blank), and then heated and pressed together before being press-molded, so the resin may be completely cured by heating. If the resin is completely cured, its ductility decreases, and there is a risk that the resin layer will break during press molding. In the case of the above-mentioned collision energy absorbing parts, if the resin layer is broken, the breakage of the main body member during axial or bending crush cannot be sufficiently prevented, so that the expected collision energy absorbing performance cannot be obtained. In addition, there is a risk of the vibration damping performance being reduced.
[0017] In contrast, the manufacturing method of Patent Document 5 involves overlapping first and second metal plates with a resin adhesive interposed between them, press-molding the resulting product, and then hardening the resin adhesive. Since the resin adhesive is not hardened during press molding, no breakage of the resin occurs. However, if the resin adhesive is press-molded without being cured, the resin adhesive may leak out from the gap between the first and second metal plates due to the surface pressure load during press molding. If the resin adhesive leaks out from between the metal plates during press molding, the inside of the mold will be contaminated with resin, making continuous production impossible.
[0018] In addition, in automotive parts that absorb the collision energy during a vehicle collision, the resin that constitutes the sandwich structure needs to have a certain thickness in order to ensure the collision energy absorption performance. However, if the resin adhesive is press-molded without being cured as in Patent Document 5, there is a problem that the resin leaks out from between the two metal plates, making it impossible to form the required resin thickness.
[0019] In response to this, Patent Document 6 describes a method in which a first body member and a second body member are joined using a damping adhesive made of resin, the damping adhesive is temporarily hardened by heating or the like, and then this joined body is joined to a third body member. This method is intended to prevent the damping adhesive from dripping when press-formed automobile parts are glued together to assemble the vehicle body, but it cannot prevent the resin from leaking (or overflowing) due to the press pressure when two metal plates with resin sandwiched between them are press-formed.
[0020] The present invention has been made to solve the above-mentioned problems, and aims to provide a method for producing automobile parts having a sandwich structure in which resin is sandwiched between steel plates (metal plates) at low cost, while preventing breakage of the resin during production. [Means for solving the problem]
[0021] The inventors have thoroughly investigated methods for preventing resin breakage and leakage (protrusion) in a manufacturing method such as that described in Patent Document 4, in which a sandwich structure is formed in a steel plate before press molding and then press molding is performed into a part shape. If the resin is heated before press molding to completely harden it, there is a risk that the resin will break during press molding. On the other hand, if heating is not performed before press molding, the resin will leak out from between the steel sheets due to the pressure applied during press molding, making it impossible to ensure the required resin thickness. Furthermore, the leaked resin may contaminate the inside of the press mold, causing problems with part molding and quality.
[0022] If resin that has been adjusted to have high viscosity and high elasticity in advance is applied, it is possible to prevent leakage of resin during press molding without having to heat the material before press molding. However, high viscosity and high elasticity resin has poor applicability, which extends the application time and reduces productivity. Another problem is that it is difficult to apply high viscosity and high elasticity resin with a uniform thickness.
[0023] The inventors therefore discovered that the above problem could be solved by applying a resin having a viscosity favorable for application to a steel plate, and then calcining this before press molding under heat treatment conditions that do not completely harden the resin. The present invention has been made based on such findings, and specifically comprises the following configurations.
[0024] (1) A method for manufacturing an automobile part according to the present invention includes a resin application step of applying a thermosetting resin to a steel sheet before forming, a patch steel plate installation process in which a patch steel plate is installed on the steel plate to which the resin has been applied so as to cover the resin; a calcination process for calcining a sandwich structural member having a sandwich structure in which the resin is sandwiched between the steel plate and the patch steel plate so that the resin has an elastic modulus of 45 MPa or more and a ductility of 10% or more; and a press molding step of press-molding the pre-sintered sandwich structural member into the shape of an automobile part.
[0025] (2) The manufacturing method of an automobile part according to the present invention includes a resin pasting step of pasting a thermosetting resin formed in a sheet shape onto a steel plate before forming, a patch steel plate installation process in which a patch steel plate is installed on the steel plate to which the resin has been applied so as to cover the resin; a calcination process for calcining a sandwich structural member having a sandwich structure in which the resin is sandwiched between the steel plate and the patch steel plate so that the resin has an elastic modulus of 45 MPa or more and a ductility of 10% or more; and a press molding step of press-molding the pre-sintered sandwich structural member into the shape of an automobile part.
[0026] (3) In addition, in the above (1) or (2), the method is characterized in that it further includes a welding process of welding the steel plate of the automotive part press-formed by the press forming process to the patch steel plate.
[0027] (4) Moreover, in the above (1) or (2), the thickness of the resin is 0.2 mm or more and 3 mm or less.
[0028] (5) Moreover, in the above (1) or (2), the resin is a thermosetting rubber-modified epoxy resin. Effect of the Invention
[0029] In the present invention, the sandwich structure member is pre-baked in such a manner that the resin has an elastic modulus of 45 MPa or more and a ductility of 10% or more, thereby making it possible to prevent both the resin from spilling out and breaking during press molding. In addition, since the sandwich structure is formed and then pressed into the part shape, the main body and patch can be press-formed at the same time, which reduces the number of processes compared to the conventional method in which each part was press-formed individually, and enables automobile parts with a sandwich structure to be manufactured at low cost. [Brief description of the drawings]
[0030] [Figure 1] 1 is an explanatory diagram of a manufacturing method for an automobile part according to an embodiment of the present invention; [Diagram 2] 1 is an external view of an automobile part to which an embodiment of the present invention is applied; [Diagram 3] 1 is a graph conceptually showing the relationship between the heating time when a thermosetting resin is heated and the viscosity, elastic modulus, and ductility of the resin. [Figure 4] FIG. 4 is an explanatory diagram of another aspect of the manufacturing method for an automobile part according to the embodiment. [Diagram 5] FIG. 1 is a diagram showing an example of the range of application (attachment) of resin according to an embodiment (part 1). [Figure 6] FIG. 2 is a diagram showing an example of the range of application (attachment) of resin according to the embodiment (part 2). [Figure 7] FIG. 4 is an explanatory diagram of an axial crushing test according to the embodiment. [Figure 8] FIG. 1 is a diagram showing a provisionally cured range of a resin in a comparative example according to an embodiment of the present invention (part 1). [Figure 9] FIG. 13 is a diagram showing a provisionally cured range of a resin in a comparative example according to an embodiment (part 2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] A manufacturing method for an automobile part according to one embodiment of the present invention is a method for manufacturing an automobile part having a sandwich structure in which resin is sandwiched between steel plates. Prior to describing this embodiment, an automobile part to which the present invention is applied will be described with reference to FIG. 2.
[0032] The automobile part 1 shown in Fig. 2 is an example of an automobile part having a sandwich structure that is the subject of the present invention. The automobile part 1 is used in body frame parts such as front side members, side sills (rockers), and center pillars, and absorbs collision energy by undergoing axial crush or bending crush when a collision load is applied to the vehicle body.
[0033] The automobile part 1 includes an outer part 3, an inner part 5 joined to the outer part 3, a resin 7 applied to the inner surface of the outer part 3, and a patch 9 covering the resin 7 and joined to the inner surface of the outer part 3.
[0034] The outer part 3 is a hat-shaped cross-section member formed from steel plate and has a top plate portion 3a, a pair of vertical wall portions 3c continuing from the top plate portion 3a via shoulder portions 3b, and flange portions 3d continuing from each of the vertical wall portions 3c. The inner part 5 is a flat member made of a steel plate, and is joined to the flange portion 3d of the outer part 3.
[0035] The resin 7 is applied to the inner surfaces of the top plate portion 3a, the shoulder portion 3b and the vertical wall portion 3c of the outer part 3. The patch 9 is made of a steel plate and is a member that prevents the resin 7 from coming off the outer part 3 when the automotive part is deformed by a vehicle collision. The patch 9 is disposed on the inside of the outer part 3 so as to cover the resin 7, and both ends of the patch 9 are welded to the inner surface of the vertical wall portion 3c of the outer part 3.
[0036] The resin 7 is bonded to the outer part 3 and the patch 9 with a predetermined adhesive strength through a calcination step S5 described below and a final baking step performed before or after the assembly of the vehicle body. The final adhesive strength after the final baking step is preferably 10 MPa or more.
[0037] The resin 7 of the automobile part 1 is not limited to one formed by applying a paint-like substance, but may be one formed by pasting a sheet-like substance with an adhesive or the like.
[0038] As described above, the automotive part 1 has a sandwich structure in which the resin 7 is sandwiched between the outer part 3 and the patch 9, which are made of steel plates. This improves the surface rigidity of the top plate portion 3a, shoulder portion 3b, and vertical wall portion 3c of the outer part 3, and prevents breakage of the steel plate in the process of axial crush or bending crush as described above, thereby improving the collision energy absorption performance of the automotive part 1. Furthermore, since the resin 7 also functions as a vibration-damping material that absorbs vibrations, the above sandwich structure improves the vibration-damping performance of the automobile part 1. Examples of the types of steel sheets used for the outer part 3, the inner part 5 and the patch 9 include cold-rolled steel sheets, hot-rolled steel sheets, stainless steel sheets, zinc-based plated steel sheets, zinc alloy-based plated steel sheets and aluminum alloy-based plated steel sheets.
[0039] In this embodiment, a method for manufacturing the above-mentioned automobile part 1 will be described. As shown in Fig. 1, the manufacturing method of the automobile part 1 in this embodiment includes a resin application step S1, a patch steel plate installation step S3, a calcination step S5, a press forming step S7, and a welding step S9. As shown in Fig. 1, in this embodiment, the resin application step S1 to the welding step S9 are performed in one press line. Figs. 1(a) to 1(f) are schematic diagrams illustrating the manufacturing process of the outer part 3 having a sandwich structure. After the welding step S9, in an assembly process performed on an assembly line, an inner part 5 is joined to the outer part 3 in Fig. 1(f), thereby manufacturing the automobile part 1 in Fig. 2.
[0040] <Resin coating process> As shown in FIG. 1(b), the resin application step S1 is a step of applying resin 7 to a steel plate 11, which is a blank material before the outer part 3 is formed. A steel sheet 11 (see FIG. 1(a)) blanked into the blank shape of an outer part 3 on the blanking line is transferred to a press line by a transfer device such as a feeder with a suction bar or a conveyor. A robot equipped with a dispenser (a device for discharging a fixed amount of liquid) is placed on the press line, and this dispenser-equipped robot applies a predetermined thickness of resin 7 to a predetermined area of a steel plate 11 transferred to the press line.
[0041] The method of applying the resin 7 is not limited to the above, and for example, the resin 7 may be applied by spraying with a spray nozzle (electrostatic coating), or the resin 7 may be applied using a brush or the like. However, coating by a coating robot using a dispenser is preferable because it can precisely supply a fixed amount of resin 7 and can apply the resin 7 to a predetermined thickness in a predetermined area of the steel plate 11.
[0042] It is desirable to set the area to which the resin 7 is applied so as to include areas that are effective in improving the collision energy absorption performance of the automobile component 1 and areas that are effective in terms of vibration damping and rigidity. For example, in the case of the automobile part 1 in Fig. 2, the presence of resin in the shoulder portion 3b of the outer part 3 during axial crushing or bending crushing can improve the collision energy absorption performance of the automobile part 1, so it is advisable to apply the resin 7 to at least the portion of the steel plate 11 that corresponds to the shoulder portion 3b. Therefore, as shown in Fig. 5(a), the resin 7 may be applied to the entire steel plate 11 except for the welded portion with the patch 9 or the inner part 5, so as to include the portion that corresponds to the shoulder portion 3b, or as shown in Fig. 6(a), the resin 7 may be applied only to the portion that corresponds to the shoulder portion 3b.
[0043] If the applied thickness of the resin 7 is thinner than 0.2 mm, it becomes difficult to apply the resin 7 uniformly. Also, if the applied thickness of the resin 7 is thicker than 3 mm, it becomes costly. For the above reasons, the thickness (applied thickness) of the resin 7 is preferably 0.2 mm or more and 3 mm or less.
[0044] The type of resin 7 may be a thermosetting type. Examples of thermosetting resins include epoxy, urethane, ester, phenol, melamine, and urea resins. In particular, thermosetting rubber-modified epoxy resins are preferable because they have high ductility after being cured by heating and therefore are less likely to break when press-molded after calcination (preheating).
[0045] <Patch steel plate installation process> As shown in Fig. 1(c), the patch steel plate installation process S3 is a process of installing a patch steel plate 13 on the steel plate 11 to which the resin 7 has been applied so as to cover the resin 7. Here, the patch steel plate is a blank material before the patch 9 (see Fig. 2) is press-formed. The steel plate 11 coated with the resin 7 in the resin coating step S1 is transferred by a transfer device to a steel plate transport robot arranged downstream of the dispenser mounting robot. The steel plate transport robot places a patch steel plate 13 at a predetermined position on the steel plate 11 so as to cover the resin 7.
[0046] Resin 7 is applied onto steel plate 11, and then a patch steel plate 13 is placed to cover it, forming a sandwich structure in which resin 7 is sandwiched between steel plate 11 and patch steel plate 13. Hereinafter, the member having this sandwich structure shown in Fig. 1(c) will be referred to as a sandwich structure member 15.
[0047] <Pre-firing process> As shown in FIG. 1(d), the calcination step S5 is a step of calcining the sandwich structural member 15 under heat treatment conditions in which the resin 7 is not completely cured. The resin 7 applied to the steel sheet 11 in the resin application step S1 is adjusted to a viscosity suitable for application. If this resin is press-formed as is without being heat-cured, the resin 7 will leak out from between the steel sheet 11 and the patch steel sheet 13 due to the pressure applied during press forming, causing problems such as the inability to ensure a specified resin thickness.
[0048] In order to prevent leakage of the resin 7 during press molding, it is necessary to heat and harden the resin 7 before press molding to bring the viscosity (or elastic modulus) to a certain level or higher. However, as mentioned above, if the resin 7 is completely hardened before press molding, the resin layer will break during press molding, and the collision energy absorption performance of the automotive part 1 will be reduced. Therefore, in the calcination step S5, the sandwich structure member 15 is calcined so that the resin 7 has physical properties suitable for press molding. The physical properties of the resin suitable for press molding will be described with reference to FIG.
[0049] In the above explanation, the term "resin leakage" has been used, but this expression assumes that the resin has fluidity (uncured state) during press molding. In this embodiment, the resin is pre-baked before press molding to lose its fluidity, so "resin leakage" is unlikely to occur during press molding after pre-baking, but if the pre-baking is insufficient, the resin may deform and protrude from between the steel sheets. If the overhang is small enough that the resin does not adhere to the mold, there is no problem in terms of production. However, if the overhang is large, the resin will adhere to the mold, making continuous production difficult, which is a problem.
[0050] In the following explanation, the phenomenon in which the resin retains fluidity during press molding and is pushed out into the mold due to the press pressure will be expressed as "resin leakage (leaking out)", and the phenomenon in which the resin loses fluidity during press molding and is exposed from between the steel plates due to the press pressure, especially the phenomenon in which the resin is exposed so much that it adheres to the mold, will be expressed as "resin protrusion". However, if the degree of resin exposure is small and the overflow is to the extent that it does not adhere to the mold, it does not cause any problems in manufacturing, and therefore is not included in the problematic "resin overflow." An example of a non-problematic overhang is a semicircular arc-shaped overhang from the edge of a steel plate in a sandwich structural component, with a length of 0.5 times the total plate thickness (mm) of the steel plate thickness before forming + resin thickness + patch steel plate thickness, and a radius (mm) of less than or equal to the length.
[0051] Fig. 3 is a graph conceptually showing the relationship between the heating time when a certain thermosetting resin is heated at 170°C and the viscosity, elastic modulus, and ductility of the resin. Note that 170°C is the heat treatment temperature when baking resin of a general structural adhesive used in the manufacture of automobiles. For reference, the baking conditions (main baking conditions) when completely curing resin of an automobile structural adhesive are generally a heating temperature of 150 to 170°C and a heating time of about 15 minutes, although they vary slightly depending on the type of resin.
[0052] As shown by curve A in Figure 3, the resin, which was liquid before heating, gradually hardens when heated, and the elastic modulus increases. At the same time, as shown by curve B, the viscosity of the resin also increases along with the elastic modulus. On the other hand, as shown by curve C, the ductility of the resin decreases in opposition to the increase in the elastic modulus. When the resin is completely cured with the passage of heating time, the change in elastic modulus and ductility becomes small and approaches a nearly constant asymptotically (curing completion region). In addition, as the thermosetting resin approaches the curing completion region, the viscosity increases exponentially, and the resin loses its fluidity and turns into a solid.
[0053] Here, the dashed arrow i in the figure indicates the range of elastic modulus of the resin 7 that can prevent the resin 7 from squeezing out when press-molding the sandwich structural member 15. In other words, if the elastic modulus indicated by the curve A is higher than the dashed arrow i, the resin can be prevented from squeezing out during press molding. Moreover, the dashed arrow ii in the figure indicates the ductility range of the resin 7 that allows the resin 7 to follow the deformation of the steel plate when press-forming the sandwich structural member 15. In other words, if the ductility indicated by the curve C is higher than the dashed arrow ii, it is possible to prevent the resin from breaking during press-forming.
[0054] If the sandwich structural member 15 is heated for a heating time (e.g., 15 minutes) under conventional main baking conditions, the resin 7 will have the properties shown in the cured region, and the resin will not squeeze out from between the steel plate 11 and the patch 9 due to the pressure applied during press forming. However, since the ductility falls below the dashed arrow ii, the resin cannot follow the deformation of the steel plate, and the resin layer will break.
[0055] Therefore, by heating the resin under heating conditions that give the resin an elastic modulus equal to or greater than the dashed arrow i and a ductility equal to or greater than the dashed arrow ii, the resin can be made to have excellent press moldability. In the example of Figure 3, by setting the heating time in the calcination step S5 to a range that is equal to or greater than the heating time t1 when curve A (elastic modulus) intersects with dashed line i and equal to or less than the heating time t2 when curve C (ductility) intersects with dashed line ii, the physical properties of the resin after heating, both the elastic modulus and ductility, will have values suitable for press molding, and both the extrusion and breakage of the resin during press molding can be prevented.
[0056] As an example of specific heat treatment conditions, it is preferable to set the heating temperature at 140 to 210°C, which is the same as the conventional main baking conditions, and the heating time at 4 to 35 seconds. By calcining under such heat treatment conditions, the viscosity of resin 7 becomes about 40 to 90% of that in the cured region, and the ductility of resin 7 becomes about 2 to 7 times that in the cured region.
[0057] Although details will be explained in the examples below, physical properties suitable for press molding, i.e., physical properties of a resin that prevent resin from extruding during press molding while also preventing resin breakage, are an elastic modulus of 45 MPa or more and a resin ductility of 10% or more. In the above, the lower limit of the elastic modulus is specified from the viewpoint of preventing the resin from protruding during press molding, and the lower limit of the ductility is specified from the viewpoint of preventing the resin from breaking during press molding, but this does not mean that there are no upper limits for the elastic modulus and ductility.
[0058] As shown in FIG. 3, the elastic modulus and ductility of a resin generally have a relationship such that, for the same resin, the greater the elastic modulus, the smaller the ductility, and vice versa. Therefore, if the lower limit of the elastic modulus is specified from the viewpoint of preventing the resin from squeezing out, the ductility value at that time (the value at heating time t1 in FIG. 3) becomes the upper limit of the ductility. Furthermore, if the lower limit of ductility is specified from the viewpoint of preventing breakage of the resin, the value of the elastic modulus at that time (the value at heating time t2 in FIG. 3) becomes the upper limit of the elastic modulus. In this way, by specifying the lower limit values of the elastic modulus and the ductility, the ranges of the elastic modulus and the ductility suitable for press forming are automatically determined.
[0059] By calcining resin 7 as described above so that it has physical properties suitable for press molding, it is possible to make the elastic modulus of resin 7 higher than when it is applied, thereby preventing the resin from overflowing during press molding, while maintaining the ductility of resin 7 at a high level, thereby preventing the resin layer from breaking during press molding. Furthermore, compared with the case where the sandwich structural member 15 is heated under conventional main baking conditions (for example, 15 minutes), the heating time is extremely short, at 4 to 35 seconds, and therefore the manufacturing time can also be shortened.
[0060] The method of calcination is not particularly limited, but possible methods include inserting the sandwich structural member 15 into a high-temperature furnace (oven) in which the atmospheric temperature is maintained constant and heating it, or heating the sandwich structural member 15 using electrical heating or high-frequency induction heating.
[0061] The above is an example in which the calcination step S5 is performed in a device such as an oven arranged on the entry side of the press machine, i.e., upstream of the press machine in the press line, but the calcination step S5 may also be performed inside the press machine as shown in Fig. 4. As a method of calcination in the case of Fig. 4, for example, a method can be considered in which a molding die used in the press molding step S7 is heated to a predetermined temperature using electrical heating or high-frequency induction heating, and the sandwich structure member 15 is placed on the heated molding die and left to stand by for a predetermined time (4 to 35 seconds).
[0062] <Press molding process> The press molding process S7 is a process for press molding the sandwich structural member 15 calcined in the calcination process S5 into a part shape of an automobile part. Here, as shown in Fig. 1(e), the sandwich structural member 15 is press molded into a part shape of the outer part 3 of the automobile part 1. Since the resin 7 has a higher viscosity than when it was applied due to the pre-firing of the sandwich structural member 15 in the pre-firing step S5, the resin 7 does not leak or protrude from between the steel plate 11 and the patch steel plate 13 even when pressure is applied during press forming. In addition, since the resin 7 is not completely cured, the resin 7 maintains a high ductility, which makes it possible to prevent the resin layer from breaking during press forming.
[0063] <Welding process> The welding step S9 is a step of welding the steel sheet 11 of the automobile component 1 press-formed in the press-forming step S7 and a patch steel sheet 13 together, as shown in FIG. 1(f). The parts press-formed in the press forming process S7 are transferred to the press machine exit side by a transfer device. A robot equipped with a spot welding gun is placed at the press machine exit side, and the patch steel plate 13 (patch 9) is spot-welded to the steel plate 11 (outer part 3) by this spot welding gun-equipped robot (the part marked with an x in FIG. 1(f)).
[0064] In addition, when the sandwich structural member 15 is press-formed, the resin 7 is subjected to high surface pressure and is pressed against the steel plate 11 and the patch steel plate 13, and then undergoes the main baking process described below, so that it is bonded to the steel plate 11 and the patch steel plate 13 with a predetermined adhesive strength, and therefore the welding process S9 can be omitted. However, the automotive part 1 of this embodiment absorbs collision energy by axial crushing or bending crushing, and if the patch 9 peels off from the resin 7 during the deformation process, the collision energy absorption characteristics will decrease, so it is preferable to fix the patch steel plate 13 to the steel plate 11.
[0065] The part in Fig. 1(f) is transferred to an assembly line, and an inner part 5 is joined to produce the automotive part 1 in Fig. 2. The resin 7 of the automotive part 1 manufactured as described above is then completely cured in a main baking process, and is then bonded to the outer part 3 and the patch 9 with a predetermined strength. An example of carrying out the main baking process using electrodeposition painting, which is commonly used in automotive manufacturing, will be described below.
[0066] After manufacturing the automobile part 1 by joining an inner part 5 to the part in Fig. 1(f), the automobile part 1 is assembled into a vehicle body. The vehicle body is immersed in an electrodeposition paint, and a paint layer is formed on the surface by electrodeposition, and then the vehicle body is transferred to a drying furnace (oven) or the like for heat treatment. The resin 7 of the automobile part 1 is completely cured by this drying heat. As described above, the drying process of the electrodeposition paint performed on the vehicle body assembled using the automobile part 1 can be positioned as the main baking process of this embodiment.
[0067] The main baking process performed on the automobile part 1 is not limited to the above, and may be performed before the assembly of the vehicle body. For example, the automobile part 1 before the assembly of the vehicle body may be heated by being placed in a high-temperature furnace (oven) in which the atmospheric temperature is kept constant, or the automobile part 1 before the assembly of the vehicle body may be heated by using electrical heating or high-frequency induction heating.
[0068] In either case, by heat treating the automotive part 1 at a predetermined temperature for a predetermined time, the resin 7 adheres to the outer part 3 and the patch 9 with a predetermined adhesive strength due to the adhesive ability of the resin itself. The heat treatment conditions in the main baking step, i.e., the heat treatment conditions for completely curing the resin 7, are a heating temperature of 150 to 170°C and a heating time of about 15 minutes, as described above. However, since the heat treatment conditions differ depending on the type of resin 7, it is advisable to adjust them appropriately so that the adhesive strength of the resin 7 after heating becomes a predetermined value (for example, 10 MPa or more).
[0069] As described above, according to this embodiment, the sandwich structural member 15 is pre-fired under heat treatment conditions that do not completely cure the resin 7, and then press-molded into the shape of the part, so that the resin 7 can be press-molded without leaking or overflowing, and breakage of the resin 7 during molding can be prevented. Therefore, an automobile part 1 having the required collision energy absorption performance and vibration damping properties can be manufactured.
[0070] Furthermore, compared to the conventional manufacturing method in which the outer part 3 and the patch 9 are press-molded separately, this embodiment allows a series of steps to be completed within a single press line, thereby improving the productivity of the automobile part 1.
[0071] In addition, since the resin 7 is applied to the steel plate 11, which is the blank material before the outer part 3 is press-formed, the resin 7 can be applied in a uniform thickness without being restricted by the uneven surface shape of the part, as compared to the case where the resin 7 is applied to a part after press forming. This makes it possible to reduce variations in the collision energy absorption performance and vibration damping performance of the automotive part 1.
[0072] The above-described manufacturing method involves applying paint-like resin 7 to the steel plate 11, but the method may also include a resin application step in which resin 7 formed in a sheet shape is applied instead of the resin application step S1. When attaching the sheet-like resin 7, for example, lamination equipment is used to attach the sheet-like resin 7 to the steel plate 11. At that time, it is preferable to temporarily fix the resin 7 to the steel plate 11 using an adhesive tape or a bonding agent. Also, when installing the patch steel plate 13 so as to cover the resin 7, it is preferable to temporarily fix the resin 7 and the patch steel plate 13 using an adhesive tape or a bonding agent. However, if the sheet-like resin 7 itself has initial adhesion, such as double-sided tape, it is not necessary to use the above-mentioned adhesive tape or bonding agent.
[0073] In addition, it has been explained that the thickness of the resin 7 to be applied is preferably 0.2 mm or more so that the resin 7 can be applied with a uniform thickness, but the thickness of the resin 7 is not limited to this when the resin 7 is applied in sheet form. The lower limit of the thickness of the resin 7 in the present invention may be any thickness that allows the resin 7 to be formed uniformly, and in the case of the resin 7 in sheet form, the sheet thickness may be about 20 μm. In addition, the upper limit of the sheet thickness of the resin 7 is preferably 3 mm or less, the same as in the case of application, from the viewpoint of cost.
[0074] Since the sheet-like resin 7 has a certain degree of hardness, it is less likely to leak during press molding compared to paint-like resin 7, but by calcining it can be adjusted to a hardness suitable for the press molding step S7 (hardness that does not cause extrusion). However, if the sheet-like resin 7 has a hardness that can withstand press molding (resin 7 does not extrude) and is not destroyed during press molding, the calcination step S5 may be omitted.
[0075] 1, the resin application step S1 to the calcination step S5 are performed in a press line that press-forms the sandwich structural member 15 into the shape of the part, but these steps do not necessarily have to be performed in the same press line. For example, a production line that manufactures the sandwich structural member 15 and a press line that press-forms the sandwich structural member 15 into the shape of the part may be provided separately. In that case, after the resin application step S1 to the calcination step S5 are performed in the production line for the sandwich structural member 15, the manufactured sandwich structural member 15 may be transferred to the press line by a transfer device, where the press forming step S7 is performed.
[0076] In addition, the welding step S9 does not necessarily have to be performed in the press line. For example, after the press forming step S7, the part shown in Fig. 1(e) may be transferred to an assembly line, and the welding step S9 may be performed when the inner part 5 is joined on the assembly line. EXAMPLES
[0077] The effects of the manufacturing method of the present invention will now be described based on specific examples. In this embodiment, resin 7 was applied or attached to a steel plate 11 having a tensile strength of 1470 MPa and a thickness of 1.4 mm as shown in Fig. 5(a) or Fig. 6(a), and then a patch steel plate 13 having a tensile strength of 270 MPa and a thickness of 0.4 mm was installed as shown in Fig. 5(b) or Fig. 6(b) to form a sandwich structural member 15. The applied thickness (or sheet thickness) of the resin 7 was set in the range of 0.2 to 3 mm. The sandwich structural member 15 was then pre-fired using various heating methods and heat treatment conditions (heating temperature 140 to 210°C, heating time 4 to 35 seconds). The heating method was either electrical heating (current flow), high-temperature furnace (oven), or mold heating (heating the molding die used in the press molding process to a predetermined temperature by electrical heating or high-frequency induction heating). FIG. 5 shows an example in which resin 7 is applied to the entire steel plate 11 (excluding the portion to be welded after press forming) (resin / area "all" in Table 1), while FIG. 6 shows an example in which resin 7 is applied only to the portion of the steel plate 11 that may become the shoulder 3b of the outer part 3 (resin / area "shoulder" in Table 1).
[0078] The above-mentioned pre-fired sandwich structural member 15 was press-molded into the part shape of the outer part 3 shown in Fig. 2, and its press formability was evaluated. Here, the presence or absence of protrusion of the resin 7 from the outer part 3 and the patch 9 after press molding was observed.
[0079] Regarding the evaluation of the overflow of resin 7, cases in which no resin overflowed from the steel plate, and cases in which the resin overflowed slightly but did not adhere to the mold were rated as "none", and cases in which the resin overflowed significantly from the steel plate and adhered to the mold were rated as "present". Specifically, any protrusion in the form of a semicircular arc with a length and radius (mm) of 0.5 times the total plate thickness (mm) of the steel plate thickness before forming + resin thickness + patch steel plate thickness from the steel plate edge of a sandwich structural component was evaluated as "none," and was distinguished from protrusion that would cause problems in manufacturing.
[0080] Thereafter, the inner part 5 was welded to the press-formed outer part 3 to assemble the automobile part 1 shown in Fig. 2, and then the assembled automobile part 1 was heated at 170°C for 15 minutes to carry out main baking. An axial crush test was then carried out on the automobile part 1 that had been main baked.
[0081] In the axial crush test, a load was applied to the automotive part 1 in the axial direction at a test speed of 17.8 m / s, and the test piece length was changed from 200 mm to 120 mm, causing an axial crush deformation of 80 mm, and the load-stroke curve was measured to determine the absorbed energy, as shown in Fig. 7. In addition, the deformation state and the presence or absence of fracture in the outer part 3 were observed using a high-speed camera. Table 1 shows the composition of each evaluation part, the heat treatment conditions for calcination, and the evaluation results of press formability and axial crush test.
[0082] [Table 1]
[0083] Inventive example A, resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in Fig. 5(a), and after the patches 9 were layered, they were pre-baked by electrical heating at 200°C for 13 seconds. The test weight was 1.17 kg, and there was no resin overflow after pressing. In addition, as a result of the axial crush test, there was no fracture of the base material (outer part 3), and the absorbed energy was 13.4 kJ, with EA / weight (energy absorbed per unit weight) being 11.5 kJ / kg.
[0084] Inventive example B, a 1 mm thick sheet-like resin 7 was temporarily fixed in the range of Fig. 5(a) with adhesive tape, and after stacking the patch 9, it was temporarily baked in an oven at 150°C for 5 seconds. The test weight was 1.21 kg and there was no resin overflow after pressing. In addition, as a result of the axial crushing test, there was no breakage of the base material, and the absorbed energy was 15.5 kJ, with EA / weight being 12.8 kJ / kg.
[0085] Inventive example C, resin 7 was applied to the area shown in Fig. 5(a) with a dispenser to a thickness of 3 mm, and then the patch 9 was layered and pre-baked for 25 seconds in a mold heated to 200°C. The test weight was 1.33 kg and there was no resin overflow after pressing. In addition, the axial crush test showed no breakage of the base material, and the absorbed energy was 18.9 kJ, with an EA / weight of 14.2 kJ / kg.
[0086] Inventive example D, resin 7 was applied with a dispenser to a thickness of 1 mm in the range shown in FIG. 6(a), and after the patch 9 was layered, it was pre-baked by electrical heating at 170°C for 8 seconds. The test weight was 1.21 kg, and there was no resin overflow after pressing. In addition, as a result of the axial crushing test, there was no breakage of the base material, and the absorbed energy was 15.5 kJ, with EA / weight being 12.8 kJ / kg.
[0087] Inventive Example E, resin 7 was applied to a thickness of 0.2 mm in the range shown in FIG. 5(a) using a dispenser, and after overlapping the patch 9, it was electrically heated at 140°C and pre-baked for 6 seconds. The test weight was 1.17 kg, and there was no resin overflow after pressing. In addition, the axial crush test showed no fracture of the base material. The absorbed energy was lower than inventive example A, but was 11.9 kJ, which was higher than comparative example A (an example without resin 7) described later, and the EA / weight was 10.2 kJ / kg.
[0088] Inventive example F is an example in which resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in FIG. 5(a), and then the patch 9 was layered and pre-baked by electrical heating at 210°C for 35 seconds. The test weight was 1.17 kg, and there was no resin overflow after pressing. In addition, the axial crush test showed no fracture of the base material. The absorbed energy was 13.0 kJ, which is higher than Comparative Example A (an example without resin 7) described later, and the EA / weight was 11.1 kJ / kg.
[0089] Inventive example G is an example in which resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in FIG. 5(a), and then the patch 9 was layered and pre-baked by electrical heating at 170°C for 4 seconds. The test weight was 1.17 kg, and there was no resin overflow after pressing. In addition, the axial crush test showed no fracture of the base material. The absorbed energy was 12.0 kJ, which is higher than Comparative Example A (an example without resin 7) described later, and the EA / weight was 10.3 kJ / kg.
[0090] Invention example H is an example in which resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in FIG. 5(a), and then the patch 9 was layered and pre-baked by electrical heating at 170°C for 15 seconds. The test weight was 1.17 kg, and there was no resin overflow after pressing. In addition, the axial crush test showed no fracture of the base material. The absorbed energy was 12.9 kJ, which is higher than Comparative Example A (an example without resin 7) described later, and the EA / weight was 11.0 kJ / kg.
[0091] Comparative Example A is an example without resin 7. In the case of Comparative Example A without a sandwich structure, the base material was fractured as a result of the axial crushing test. In addition, the absorbed energy was 10.7 kJ, and the EA / weight was 9.2 kJ / kg.
[0092] Comparative Example B is an example in which resin 7 is present but is not pre-baked. The resin that is applied without pre-baking is prone to overflow during press processing. In addition, there was a concern that the highly fluid resin would scatter around and damage the equipment and measuring instruments, so an axial crush test was not performed.
[0093] Comparative Example C is an example in which resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in FIG. 5(a), and then the patch 9 was layered and baked in an oven at 170°C for 900 seconds (15 minutes). The test weight was 1.17 kg, and there was no resin overflow after pressing. However, the axial crush test showed that the base material was broken, and there was almost no increase in absorbed energy compared to Comparative Example A.
[0094] Comparative Example D is an example in which resin 7 was applied with a dispenser to a thickness of 0.2 mm in the range shown in Figure 5(a), and then patches 9 were layered on top of each other and pre-baked at 170°C for 45 seconds by electrical heating. The test weight was 1.17 kg and there was no resin overflow after pressing. In addition, the axial crush test showed that the base material was broken, and there was almost no increase in absorbed energy compared to Comparative Example A.
[0095] As described above, no overflow of resin 7 occurred during press molding in any of Examples A to H. In addition, although the presence or absence of breakage of resin 7 during press molding cannot be visually evaluated, all of Examples A to H exhibited higher energy absorption performance than Comparative Examples A to D.
[0096] Moreover, the elastic modulus and ductility of the resin after calcination in each example in Table 1 were examined by the following method. First, the gap between two steel plates was adjusted to 0.2 mm, uncured resin was placed between them, and the plates were heated under each of the pre-firing conditions in Table 1. After that, the steel plates were peeled off to produce a 0.2 mm-thick resin-on-plate. Next, the flat resin was processed into a dumbbell shape (JIS No. 6 dumbbell) to prepare a test piece, and a tensile test was performed at a tensile speed of 2 mm / min until the resin broke. The elongation between the gauge lines at the time the resin broke was divided by the initial gauge line distance (= 20 mm) to calculate the elongation as a percentage, which was regarded as the ductility of the test piece. Further, from the stress-strain curve obtained by the tensile test, the slope of the stress (tensile strength) between strain amounts of 0 and 0.005, which is the elastic region, was calculated and defined as the elastic modulus of the test piece. The results are also shown in Table 1.
[0097] As described above, the elastic modulus and ductility of the resin after calcination under each calcination condition were measured, and it was found that the elastic modulus was 45 MPa or more and the ductility was 10% or more. In other words, if the physical properties of the resin after calcination are an elastic modulus of 45 MPa or more and a ductility of 10% or more, as shown in Table 1, there will be no resin overflow when the sandwich structural component is press-molded, and the resin will exhibit high energy absorption performance in an axial crush test (no resin breakage will occur).
[0098] In addition, looking at Comparative Examples B to D, none of them satisfied the conditions of elastic modulus of 45 MPa or more and ductility of 10% or more, and when the elastic modulus was less than 45 MPa, resin overflow occurred, and when the ductility was less than 10%, resin breakage occurred. Therefore, when the condition of either elastic modulus or ductility is not satisfied, both the overflow and breakage of the resin during press molding cannot be prevented.
[0099] As described above, it was found that by pre-firing the sandwich structural components and then press-molding them so that the physical properties of the resin after pre-firing are an elastic modulus of 45 MPa or more and a ductility of 10% or more, it is possible to suppress resin extrusion and breakage during press molding.
[0100] The test pieces used in the tensile test were prepared under conditions where the resin thickness was the thinnest within the range of resin thickness (0.2 mm to 3 mm) specified by the present invention, that is, where the ductility was assumed to be the smallest. Therefore, if the resin thickness is within the range specified by the present invention, it is considered that the ductility will not fall below that shown in Table 1 when calcined under the same heating conditions, and no breakage of the resin will occur.
[0101] Incidentally, the above-mentioned Patent Document 6 discloses a technique for preventing resin dripping due to gravity by partially temporarily curing the resin. Therefore, we investigated whether such a technique can also prevent resin from spilling out during press molding, and the results are shown in Table 2.
[0102] [Table 2]
[0103] Comparative Examples E to H in Table 2 are comparative examples relating to the technology of Patent Document 6, in which the resin thickness, range in which the resin is provided, heating temperature, and heating time are the same as those of Invention Examples A to D in Table 1, and only the range in which the resin is hardened is limited. Patent Document 6 describes that the resin in the portion that will become the lower end region in the assembled position is provisionally hardened, but in Comparative Examples E to H, the resin in the outer periphery of the applied (applied) resin is provisionally hardened, as shown in Figs. 8 and 9. FIG. 8 shows an example in which resin 7 is applied to the entire steel plate 11 (excluding the portion to be welded after press forming) (resin / area "all" in Table 2), while FIG. 9 shows an example in which resin 7 is applied only to the portion of the steel plate 11 that may become the shoulder 3b of the outer part 3 (resin / area "shoulder" in Table 2). As for the heating method, high-frequency induction heating was used with reference to Patent Document 6.
[0104] The sandwich structural member 15 in which only the outer peripheral portion of the resin 7 had been provisionally hardened as described above was press-molded into the part shape of the outer part 3 shown in Figure 2, and its press moldability, i.e., the presence or absence of resin 7 protruding from the outer part 3 and patch 9 after press molding, was evaluated.
[0105] As a result, as shown in Table 2, none of Comparative Examples E to H was able to suppress the extrusion of resin during press molding. This is thought to be because strong pressure was applied to the resin during press molding, causing the temporarily hardened parts to break as they were unable to withstand the internal pressure.
[0106] As described above, the technique of Patent Document 6 is effective in preventing resin sagging due to gravity, but cannot prevent resin protrusion caused by strong pressure during press molding. Therefore, even when compared with the technology of Patent Document 6, the present invention has been shown to be superior as a method for manufacturing automobile parts having a sandwich structure. [Explanation of symbols]
[0107] 1. Automotive parts 3 Outer parts 3a Top plate 3b Shoulder 3c Vertical wall section 3d flange part 5 Inner parts 7. Resin 9 Patch 11 Steel plate 13 Patch Steel Plate 15 Sandwich structural members
Claims
1. a resin application process for applying a thermosetting resin to the steel plate before forming; a patch steel plate installation process in which a patch steel plate is installed on the steel plate to which the resin has been applied so as to cover the resin; a calcination process for calcining a sandwich structural member having a sandwich structure in which the resin is sandwiched between the steel plate and the patch steel plate so that the resin has an elastic modulus of 45 MPa or more and a ductility of 10% or more; and a press molding step of press-molding the pre-sintered sandwich structural member into the shape of an automobile part.
2. a resin application process for applying a thermosetting resin formed in a sheet shape to the steel plate before forming; a patch steel plate installation process in which a patch steel plate is installed on the steel plate to which the resin has been applied so as to cover the resin; a calcination process for calcining a sandwich structural member having a sandwich structure in which the resin is sandwiched between the steel plate and the patch steel plate so that the resin has an elastic modulus of 45 MPa or more and a ductility of 10% or more; and a press molding step of press-molding the pre-sintered sandwich structural member into the shape of an automobile part.
3. 3. The method for manufacturing an automobile part according to claim 1, further comprising a welding step of welding the steel plate of the automobile part press-formed in the press forming step to the patch steel plate.
4. 3. The method for manufacturing an automobile part according to claim 1, wherein the thickness of the resin is 0.2 mm or more and 3 mm or less.
5. 3. The method for manufacturing an automobile part according to claim 1, wherein the resin is a thermosetting rubber-modified epoxy resin.
Citation Information
Patent Citations
Method for producing a hybrid component made of sheet metal and fibre-reinforced composite material
EP3085509A1
Production of innmold decorated molding
JP1981084668A
METHOD FOR MANUFACTURING FIBER REINFORCED COMPOSITE MATERIAL PARTS
JP2008532820A
Method for manufacturing semi-finished products or components containing a metal carrier, and a curable coating comprising fiber-reinforced plastic.
JP2015520027A
Carbon fiber reinforced plastic composite metal plate for vehicle and vehicle panel
JP7260836B2